Electrocatalytic H2 evolution promoted by a bioinspired (N2S2)Ni(ii) complex. Issue 8 (4th January 2022) - Sinha, Soumalya; Tran, Giang N.; Na, Hanah; Mirica, Liviu M.
Abstract : We report a bioinspired (N2S2)Ni(ii ) complex that catalyzes the electrochemical H2 evolution reaction (HER) with a turnover frequency (TOF) of ∼1250 s −1 at low acid concentration in acetonitrile. Abstract : A bioinspired (N2S2)Ni(ii ) electrocatalyst is reported that produces H2 from CF3 CO2 H with a turnover frequency (TOF) of ∼1250 s −1 at low acid concentration (<0.043 M) in MeCN. A mechanism for the H2 production by this electrocatalyst is proposed and its activity is benchmarked against those of other reported molecular Ni H2 evolution electrocatalysts. The involvement of a hemilabile pyridyl group of the N2S2 ligand is proposed to mimic the role of a cysteine residue involved in the biological proton reduction performed by [NiFe] hydrogenases.